Automated production of [18F]SiTATE on a Scintomics GRP™ platform for PET/CT imaging of neuroendocrine tumors - Lindner, Simon; Simmet, Marcel; Gildehaus, Franz-Josef; Jurkschat, Klaus; Wängler, Carmen; Wängler, Björn; Bartenstein, Peter; Schirrmacher, Ralf; Ilhan, Harun (Nuclear medicine and biology, 2020)
Introduction - [18F]SiTATE (formerly known as [18F]SiFAlin-TATE) was recently introduced as a highly promising imaging agent for the diagnosis of well-differentiated neuroendocrine tumors (NET) using positron emission tomography/computed tomography (PET/CT). A high tumor uptake and excellent image quality, the straightforward labeling approach, as well as the economic and logistic advantages of 18F- over 68Ga-labeled compounds predestinate [18F]SiTATE to become a potential new clinical reference standard. A novel state-of-the-art methodology of automated radiopharmaceutical production is required to establish [18F]SiTATE in clinical routine. This work illustrates the development of a novel synthesis procedure of [18F]SiTATE on an automated synthesis unit (ASU) and the clinical applicability of the tracer in human NET imaging. - Methods - A new synthesis protocol was generated for the production of [18F]SiTATE on the Scintomics GRP™ platform for clinical NET imaging. The synthesis was carried out according to common Good Manufacturing Practice (GMP) guidelines including all quality control measurements. To confirm utility, clinical batches (n = 3) were produced and applied to six patients diagnosed with NET. - Results - [18F]SiTATE was obtained in 54 ± 4% (n = 3) non-decay corrected radiochemical yield (RCY), with a radiochemical purity of 96.3 ± 0.1% and a molar activity (Am) of 472 ± 45 GBq/μmol (n = 3). Quality control measurements always met the local release criteria. All specifications were taken or adapted from the Ph.Eur. regulations. PET/CT imaging with [18F]SiTATE produced on the GRP™ module confirmed the expected high image quality. The in vivo distribution pattern and excellent tumor to non-tumor contrast observed, matched the quality of the manually prepared [18F]SiTATE batches. - Conclusions - The automated manufacture of [18F]SiTATE was developed using the Scintomics GRP™ platform. The high quality of the radiotracer matched stringent quality control requirements adhering to common GMP guidelines, and its clinical applicability was confirmed by human PET/CT investigations. - Advances in knowledge and implications for patient care - The automated process for the manufacture of [18F]SiTATE described herein represents an important contribution to make [18F]SiTATE routinely accessible for its use in clinical NET diagnosis.